Clinically-diagnosed Mediterranean Spotted Fever in Malta. Issue 26 (November 2018) - Torpiano, Paul; Pace, David
Abstract: Background: Mediterranean Spotted Fever (MSF) is a tick-borne zoonosis caused by Rickettsia conorii which is endemic in Malta, an island in the South Mediterranean that is a popular tourist destination. Diagnosis is frequently based on clinical manifestations as laboratory results are often limited to a retrospective diagnosis. We describe the clinical presentation, diagnosis and treatment of children <16 years who presented with MSF from 2011 to 2016. Method: The demographics, clinical findings, laboratory results, management and outcome of all children hospitalised with suspected MSF based on the presence of fever and an eschar, were retrieved from their case notes. Results: Over the five-year study period six children, aged between 17 months and 15 years, were diagnosed with MSF. All children had contact with ticks and the majority presented in summer. Laboratory results were non-specific and included elevated inflammatory markers, lymphocytosis/lymphopenia and hyponatraemia. Serological and molecular techniques were used for diagnosis. Response to clarithromycin or doxycycline was immediate. Conclusion: MSF should be included in the differential diagnosis of fever, rash and an eschar in children who travel to Malta. Despite advances in molecular diagnostics, clinical diagnosis remains important in the management of children with suspected MSF.